The Journal of Headache and Pain Official Journal of the "European Headache Federation" and of "Lifting The Burden - The Global Campaign against Headache" - Martelletti, Paolo
The Journal of Headache and Pain is a peer-reviewed open access journal published under the brand SpringerOpen. It is specifically dedicated to researchers involved in all aspects of headache and related pain, including theory, methodology, clinical practice and care. The journal's scope is broad, reflecting the wide application of scientific advances to every branch of headache and related pain management. Within a multidisciplinary perspective, The Journal of Headache and Pain covers headache and related pain syndromes in the following fields: genetics, neurology, internal medicine, clinical pharmacology, child neuropediatrics, anesthesiology, rheumatology, otology, dentistry, neurotraumatology, neurosurgery, psychiatry, pain management, addiction, public health, and epidemiology.